2019
DOI: 10.1007/s11010-019-03581-0
|View full text |Cite
|
Sign up to set email alerts
|

Apelin promotes hepatic fibrosis through ERK signaling in LX-2 cells

Abstract: Apelin participates in cardiovascular functions, metabolic disease, and homeostasis disorder. However, the biological function of apelin in liver diseases, especially liver fibrosis is still under investigation. The present study aimed to investigate the expression of apelin in nonalcoholic fatty liver disease (NAFLD) and the mechanism of apelin promoting hepatic fibrosis through ERK signaling in hepatic stellate LX-2 cells. The results showed that the ALT and AST levels in serum were increased in the mice fed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 39 publications
1
22
0
Order By: Relevance
“…The expression of phos-ERK is positively correlated with the expression of alpha-SMA in HCC patients [36]. In hepatic cell line, apelin could activate ERK signaling to increase alpha-SMA, collagen I and cyclin D1 [37]. ERK signaling could activate type I collagen in fibroblasts [38].…”
Section: Discussionmentioning
confidence: 99%
“…The expression of phos-ERK is positively correlated with the expression of alpha-SMA in HCC patients [36]. In hepatic cell line, apelin could activate ERK signaling to increase alpha-SMA, collagen I and cyclin D1 [37]. ERK signaling could activate type I collagen in fibroblasts [38].…”
Section: Discussionmentioning
confidence: 99%
“…For example, apelin is upregulated in the intestinal epithelial cells of IBD patients and highly expressed in the mesenteric adipose tissue of Crohn’s disease patients[ 27 , 28 ]. Another study group showed that apelin is promoting hepatic fibrosis[ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…In vitro, apelin has also demonstrated a significant potential to promote liver fibrosis. It acts directly on LX-2 cells (a cell line used as a reliable in vitro model of HSC) through Erk signalling [179], stimulating cell survival and the synthesis of PDGF-β receptor and collagen-I in these cells [118]. In turn, PDGF-β and LPS can stimulate the expression of APJ, expanding and perpetuating HSC activation [180].…”
Section: Involvement Of the Apelin System In The Pathogenesis Of Lmentioning
confidence: 99%